Evaluation of Foreign Direct Investment in Insurance Sector in India (International Journal of Food and Nutritional Sciences, 2022)
The idea of what constitutes a "foreign" entity is deeply ingrained in virtually every part of the Indian mentality. This word, which in the popular mind connotes modernization, foreign brands, and acquisitions by MNCs, has received additional significance as a result of the reforms that were launched by the Indian Government in the year 1991. These types of investments are "usually preferred over other forms of external finance because they are non-volatile and their returns depend on the performance of the projects financed by the investors." Also, foreign direct investment helps to ease the process of international trade as well as the exchange of knowledge, expertise, and technology. The importance of direct investment from foreign companies to the expansion of the global economy is expanding. This study focuses primarily on the topic of FDI in the insurance sector as well as the importance of FDIC to the Indian insurance industry. Although though the economy is in a downward trend, the insurance industry in India has a significant amount of untapped potential, and it is anticipated that the flow of foreign direct investment would increase in the near future. This study will aim to present the current state of foreign direct investment in India's insurance business.